إدارة التغيير كأداة لتفعيل عملية الخوصصة - حالة الجزائر - أحمد قايد, نورالدين (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
الخوصصة ليست هدفا في حد ذاته، إنما هي وسيلة لتحقيق كفاءة الاقتصاد الوطني عن طريق تحسين أداء المؤسسات الاقتصادية. حيث يتطلب تحسين أداء هذه المؤسسات إحداث تغييرات جذرية عديدة في كافة عناصر المؤسسة سواء كانت تقنية، هيكلية، مادية أو بشرية، الهدف من وراءها هو تصحيح الخلل في عناصر عدم الكفاءة، وعليه فإن الخوصصة تعتبر بمثابة الانتقال من نموذج تسيير إلى نموذج تسيير مغاير من حيث المبادئ والأهداف والقيادة والتقنيات المستخدمة. وحتى تتم هذه التغييرات التنظيمية بنجاح يجب اختيار الأسلوب المناسب للخوصصة الذي يتلاءم وظروف وخصائص المؤسسة، وكذا يجب توفير المتطلبات القانونية، الاجتماعية، السياسية والاقتصادية التي من شأنها أن تعزز النجاح، إضافة إلى ذلك يجب إدارة هذا التغيير من خلال تشخيص نقاط القوة والضعف لدى المؤسسة وما يقابلها من فرص وتهديدات بعد عملية التغيير، وكذا يجب مراعاة آثار عملية الخوصصة على كل الأطراف في المؤسسة. الكلمات المفتاحية : إدارة التغيير، الخوصصة، الملكية العامة، الملكية الخاصة. Abstract: Privatization is not an end in itself, but rather a means to achieve the efficiency of the national economy by improving the performance of economic enterprises. It requires bringing many radical changes to all elements of the enterprise, whether they are technical, structural, material or human, of which the aim is to correct an imbalance in the elements of efficiency, and therefore the privatization is considered to be the transition from a run model to another run model different in terms of principles, objectives, leadership and used techniques. And to make these regulatory changes successful, we should choose the appropriate method of privatization, which suits the conditions and characteristics of the enterprise, as well as providing the legal requirements, as well as the social, political and economic ones, that would enhance this success, but also, we must manage the change by diagnosing strengths and weaknesses of the enterprise and the corresponding opportunities and threats after the change process, as well as taking into account the effects of the privatization process on all parties in the enterprise. Keywords : change management, privatization, public ownership, private property.